Optimizing post activation potentiation for explosive activities in competitive sports - Golas, A.; Maszczyk, A.; Zajac, A.; Mikolajec, K.; Stastny, P. (Journal of Human Kinetics, 2016)
Post activation potentiation (PAP) has shown improved performance during movements requiring large muscular power output following contractions under near maximal load conditions. PAP can be described as an acute enhancement of performance or an enhancement of factors determining an explosive sports activity following a preload stimulus. In practice, PAP has been achieved by complex training, which involves a combination of a heavy loaded exercise followed by a biomechanically similar explosive activity, best if specific for a particular sport discipline. The main objective of this study was to investigate the effects of PAP on performance in explosive motor activities specific for basketball, luge and athletics throws. The novel approach to the experiments included individualized recovery time (IRT) between the conditioning exercise and the explosive activity. Additionally, the research groups were homogenous and included only competitive athletes of similar age and training experience. Thirty one well trained athletes from 3 different sport disciplines participated in the study. All athletes performed a heavy loaded conditioning activity (80-130%1RM) followed by a biomechanically similar explosive exercise, during which power (W) or the rate of power development (W/s/kg) was evaluated. The results of our experiment confirmed the effectiveness of PAP with well-trained athlets during explosive motor activities such as jumping, throwing and pushing. Additionally, our research showed that eccentric supramaximal intensities (130% 1RM) can be effective in eliciting PAP in strength trained athletes. Our experiments also showed that the IRT should be individualized because athletes differ in the strength level, training experience and muscle fiber structure. In the three experiments conducted with basketball players, track and field athletes and luge athletes, the optimal IRT equaled 6 min. This justifies the need to individualize the volume and intensity of the CA, and especially the IRT, between the CA and the explosive activity.